2022
DOI: 10.4018/jbe.309126
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Business Ecosystem Dynamics Using Agile Structuration Theory

Abstract: The authors' background interest is in innovation and entrepreneurship as elements of business strategy.  Business ecosystems are viewed as complex adaptive systems, and engagement with such systems is explored utilising an analytical technique  based on an agile structuration theory model.  In this model, motivated knowledgeable agents act within an institutional (structuration) framework to implement a business idea, drawing on accessible resources from a broader business ecosystem and then learn from the ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…In closing this case study analysis, Moreso faced the challenges of declining sales to over 85% because of the COVID-19 pandemic. The review of existing literature showed the need for organizationstobuildanadaptiveculture (Krishnan,2018;Schein&Schein,2017).Accordingto Beckett and O'Loughlin (2022) Economic challenges such as scaling departmental budgets faced with additional pressure to maximize marketing expenses are critical reasons for technological changes for real estate developmentbusinesses.Areductioninadvertisementcostsandmoreemphasisonmultimedia promotion and marketing practices are vital competencies needed for success in real estate development.DuetoaCOVIDenvironment,budgetcostscouldpotentiallyresultinseveraljob losses or restructuring positions for a lack of productivity in the long-term goals of marketing deliverables and milestones. Exploring the literature and client organizational development engagement developed several significant themes of areas where the organization focused and improved its performance.…”
Section: Step 2 Data Analysis and Diagnosismentioning
confidence: 99%
“…In closing this case study analysis, Moreso faced the challenges of declining sales to over 85% because of the COVID-19 pandemic. The review of existing literature showed the need for organizationstobuildanadaptiveculture (Krishnan,2018;Schein&Schein,2017).Accordingto Beckett and O'Loughlin (2022) Economic challenges such as scaling departmental budgets faced with additional pressure to maximize marketing expenses are critical reasons for technological changes for real estate developmentbusinesses.Areductioninadvertisementcostsandmoreemphasisonmultimedia promotion and marketing practices are vital competencies needed for success in real estate development.DuetoaCOVIDenvironment,budgetcostscouldpotentiallyresultinseveraljob losses or restructuring positions for a lack of productivity in the long-term goals of marketing deliverables and milestones. Exploring the literature and client organizational development engagement developed several significant themes of areas where the organization focused and improved its performance.…”
Section: Step 2 Data Analysis and Diagnosismentioning
confidence: 99%